DIGITAL CURRENCIES, SWOT ANALYSIS - Kjartan Sigurðsson; Grétar Þór Eyþórsson; Helga Kristjánsdóttir (Baltic Journal of Economic Studies, 2023)
Abstract. The paper highlights the increased international trade and discussion in recent years of digital currencies, also known as virtual currencies or cryptocurrencies, including the bilateral trade coin bitcoin (BTC). Scholars have emphasised the need to consider different preconditions, focusing primarily on domestic perspectives of payment intermediation within individual countries. The inclusion of digital currencies in global trade is motivated by the recognition that time is playing an increasingly important role in trade dynamics. Scholars have presented arguments on the potential impact of CBDCs (central bank digital currencies), highlighting their ability to facilitate secure and seamless payment transactions in line with the primary objective of central banks. Conversely, sceptics argue that the mere issuance of CBDCs can potentially undermine the stability of the financial system. High interest rates tend to reduce the amount of cash in circulation. Therefore, higher interest rates do not stimulate digital currencies as investors seek to keep their funds tied up rather than floating. The purpose of this research is to consider the concept of digital currencies in global trade, reflecting the increasing importance of time in trade. Older generations have been reluctant to embrace this new way of doing business, and many questions have arisen. For example, digital currencies compete with traditional currencies, making government control difficult. There are also issues of trust, credibility, volatility, use across countries, use across time zones, trading time, uncertainty, disruption to current centralised economic systems, lender of last resort in the form of a central bank, as well as distance and culture in international trade. The methodology used is the well-known and classic SWOT analysis, which provides tools for analysing the pros and cons of digital currencies. It sheds light on the advantages and disadvantages of digital currencies, including strengths, weaknesses, opportunities and threats. The results vary depending on the weight of the four measures provided. The practical implications are that it is important to be aware of the measured factors when trading: Strengths, Weaknesses, Opportunities and Threats. Finally, it is believed that the value/originality of the research sheds light on issues that people need to be aware of when considering entering into a transaction using some form of digital currency.